Effect of testing conditions on the dry sliding behavior of a Cu-Based refractory composite material. (December 2019) - Jayashree, Priyadarshini; Turani, Simone; Straffelini, Giovanni
Abstract: Dry sliding tests were conducted at room temperature and 400 °C on a copper-tungsten composite material paired with martensitic stainless steel disc. The friction coefficient was seen to reduce for room temperature tests at high velocity, whereas it increased for high-temperature tests for the same testing conditions. The pin wear reduced with an increase in velocity and was always mild in nature. High oxide coverage, containing copper and iron were seen on the surface of the friction material as well as counterface. The magnitude of the coverage increased with velocity and temperature. Yates' statistical method was utilized to analyze parameters that influenced the friction coefficient, pin wear and the (Cu + Fe)/O ratio, in comparison with a reference copper-tin based composite. Highlights: Dry sliding of a Cu–W composite paired with conventional martensitic stainless steel disc. Sliding at two velocities and at ambient as well as 400 °C. Friction and wear depend on the characteristics of the friction layer. Yates' method was utilized to analyze the influence of the parameters.